Uma nova abordagem de big data através da implementação do software RAID - Amorim, Catarina Jacinto Nunes da Costa (2019)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence